2013
DOI: 10.1093/neuonc/not234
|View full text |Cite
|
Sign up to set email alerts
|

Induced interleukin-33 expression enhances the tumorigenic activity of rat glioma cells

Abstract: Accordingly, we concluded that glioma cells with abundant production of IL-33 grow rapidly; moreover, the interactions of multiple cytokines/chemokines induced by glioma cells may develop a microenvironment that facilitates microglia/macrophage infiltration and fosters glioma growth in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…The proposed mechanism responsible for the enhanced tumour growth was the increase in the number of infiltrating immunosuppressive immune cells and innate lymphoid cells, providing further evidence of the role of IL-33 in driving carcinogenesis [95]. Consistent with a role for IL-33 and ST2 in promoting tumour metastasis and invasion, inhibition of IL-33 and ST2 in glioma cells resulted in reduced tumour growth and colony formation in vitro, and reduced tumour size in vivo [96]. In head and neck squamous cell carcinoma (HNSCC), it has been shown that administration of IL-33 promoted cancer cell migration and invasion through induction of epithelial-mesenchymal transition [97].…”
Section: "Wounds That Do Not Heal" -Understanding the Role Of Il-33 Imentioning
confidence: 69%
“…The proposed mechanism responsible for the enhanced tumour growth was the increase in the number of infiltrating immunosuppressive immune cells and innate lymphoid cells, providing further evidence of the role of IL-33 in driving carcinogenesis [95]. Consistent with a role for IL-33 and ST2 in promoting tumour metastasis and invasion, inhibition of IL-33 and ST2 in glioma cells resulted in reduced tumour growth and colony formation in vitro, and reduced tumour size in vivo [96]. In head and neck squamous cell carcinoma (HNSCC), it has been shown that administration of IL-33 promoted cancer cell migration and invasion through induction of epithelial-mesenchymal transition [97].…”
Section: "Wounds That Do Not Heal" -Understanding the Role Of Il-33 Imentioning
confidence: 69%
“…Interestingly, this study provides evidence that pSmad1/5/8 may correlate with pSmad2 levels (Figure 3) and TGF-β 1 protein levels (Figure 3) and that high pSmad1/5/8 protein levels are associated with inferior survival (Supplementary Figure 8 and 10). These observations call for further studies on the role of pSmad1/5/8 in glioblastoma, e.g., BMP antagonists may protect tumor cells from BMP-induced, pSmad1/5/8-mediated differentiation [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Using ST2-deficient mice, a reduction was shown in tumor progression and metastasis as compared to WT mice was accompanied by increased numbers of intra-tumor CD4 + , CD8 + T lymphocytes and NK cells [86]. Similarly, inhibition of IL-33 using a lentivirus-mediated gene knockdown in a rat model of glioma attenuated tumor progression [87]. On the other hand, IL-33 may be involved in promoting the epithelial-mesenchymal transition which drives tumor invasion and migration [88].…”
Section: Cancermentioning
confidence: 99%